INTEGRATION OF ADOBE PHOTOSHOP AND THE GOOGLE ARTS & CULTURE PLATFORMS INTO THE EDUCATIONAL PROCESS OF FUTURE FINE ARTS TEACHERS (Scientific journal of the Fergana State University, 2026)
The article examines modern methods and technologies used in the professional and methodological training of future fine arts teachers. Special attention is given to the integration of digital tools, such as Adobe Photoshop and Google Arts & Culture, as well as innovative approaches, including project-based learning, individual and differentiated instruction. The results of the experiment confirm the effectiveness of implementing innovative methods that contribute to the development of students' professional and creative skills. Challenges related to resource accessibility and the need to improve teacher qualifications have been identified, and recommendations for integrating modern approaches into teacher training are proposed.